2016
DOI: 10.1089/ars.2015.6532
|View full text |Cite
|
Sign up to set email alerts
|

Menadione-Induced DNA Damage Leads to Mitochondrial Dysfunction and Fragmentation During Rosette Formation in Fuchs Endothelial Corneal Dystrophy

Abstract: Aims: Fuchs endothelial corneal dystrophy (FECD), a leading cause of age-related corneal edema requiring transplantation, is characterized by rosette formation of corneal endothelium with ensuing apoptosis. We sought to determine whether excess of mitochondrial reactive oxygen species leads to chronic accumulation of oxidative DNA damage and mitochondrial dysfunction, instigating cell death. Results: We modeled the pathognomonic rosette formation of postmitotic corneal cells by increasing endogenous cellular o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
73
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 68 publications
(84 citation statements)
references
References 45 publications
10
73
0
1
Order By: Relevance
“…Mitochondria are the main source of cellular energy metabolism. Mitochondrial mass is decreased in the Fuchs endothelial corneal dystrophy, and the corneal endothelial cells subjected to oxidative stress (Halilovic et al, 2016). The abundance of mitochondria in the corneal endothelial cells is essential for maintaining corneal hydration and transparency.…”
Section: Discussionmentioning
confidence: 99%
“…Mitochondria are the main source of cellular energy metabolism. Mitochondrial mass is decreased in the Fuchs endothelial corneal dystrophy, and the corneal endothelial cells subjected to oxidative stress (Halilovic et al, 2016). The abundance of mitochondria in the corneal endothelial cells is essential for maintaining corneal hydration and transparency.…”
Section: Discussionmentioning
confidence: 99%
“…treatment leads to rosette formation, mitochondrial dysfunction and activation of apoptosis in FECD cells 13 . Moreover, subsequent work by the same group showed that the loss of mitochondria in FECD would be caused by the activation of mitophagy 14 .…”
mentioning
confidence: 97%
“…Several reports suggest a strong association between mitochondrial DNA damage and aging [41]. Halilovic et al have shown that mechanism of endothelial cell death in FECD was due to increased generation of superoxide in mitochondria and loss of adenosine triphosphate (ATP) [42]. The same study also showed that oxidative DNA damage causes degeneration of endothelial cells in FECD.…”
Section: Rosmentioning
confidence: 95%